SharePoint 2013 WCM advanced cookbook : over 110 recipes to engineer web content and master SharePoint 2013 - Chapman, John. (Birmingham, UK : Packt Pub., 2014)
You will be led carefully step-by-step through a detailed set of recipes. This book focuses on web content management using Microsoft SharePoint 2013 server. The practical examples are built logically throughout the chapters to create a common theme. This book is ideal for developers who want to broaden their understanding of the web content management features available with SharePoint 2013. It is assumed that you already have some experience using SharePoint and developing web content. Experience with Microsoft PowerShell and coding C# with Visual Studio will also be helpful, but is not esse.
Adding localization to a SharePoint solutionCreating a site feature to apply branding; Creating the site collection feature to apply the feature to new and existing sites; Creating a timer job to ensure the site branding feature is activated; Packaging and deploying the SharePoint solution; Activating the site collection feature on all site collections with PowerShell; Chapter 5: Enhancing the Content Creation Process with the SharePoint Publishing Architecture; Introduction; Setting up a new publishing site; Enabling the publishing features on an existing site
Online resource; title from cover (Safari, viewed February 10, 2014).
English.
Added to collection customer.56279.3
Keywords: Microsoft SharePoint (Electronic resource); Microsoft SharePoint (Electronic resource); Microsoft SharePoint (Electronic resource); Intranets (Computer networks); Web servers; Web sites -- Management; Intranets; Serveurs Web; Sites Web -- Gestion; intranets; COMPUTERS -- General; COMPUTERS -- Networking -- Intranets & Extranets; COMPUTERS -- Web -- General; Intranets (Computer networks); Web servers; Web sites -- Management